Phytotoxicity of plant extracts of Vismia japurensis cultivated in vivo and in vitro - L. M. Lima; L. S. Pedroza; M. I. C. Osório; J. C. Souza; C. V. Nunez (Brazilian Journal of Biology, 2021)
Abstract Plants that produce secondary metabolites with allelopathic activity or phytotoxicity can be biotechnologically important, serving as sources of allelochemicals, and thus contributing to the agroindustrial sector. Vismia japurensis (Hypericaceae) is an Amazonian species that grows in clumps called vismiais, from which most other plants are absent. Accordingly, the objective of this study was to identify possible phytotoxicity effects of hexane and methanol extracts of Vismia japurensis leaves and branches in vivo and from seedlings grown in vitro on Lactuca sativa. In addition, fresh and dry leaves were assayed by the sandwich method in order to determine their ability to release allelochemicals. The hexanic extract from in vitro seedlings reduced germination by 10%, while the methanol extract produced a 16% reduction in germination speed. Root growth of Lactuca sativa was inhibited by 64.7% when subjected to hexane leaf extract, by 39.3% under the influence of hexane branch extract, and by 96.09% for in vitro seedling hexanic extract. When analysed by thin layer chromatography and 1H nuclear magnetic resonance, extracts showed evidence of terpenes, anthraquinones and flavonoids, with greater intensity of signals in the aromatic region of in vitro seedling hexanic extract. Clearly, Vismia japurensis has a high biotechnological potential in terms of the production of substances of low polarity with capacity to interfere in plant development.